THE EFFECT OF ETHANOL EXTRACT OF PIRDOT (Saurauria vulcani) ON HEMATOLOGICAL PROFILE AND KEAP1-NRF2 INHIBITION OF WHITE RATS INDUCED RHODAMINE B - Adriana Yulinda Dumaria Lumban Gaol; Erlintan Sinaga; Rosinta Febryanti Simamora; Feimmy Ruth Pratiwi Sipahutar; Hudson Sidabutar (Universitas Negeri Medan, 2023)
The study was designed to evaluate the hematological effect of ethanol extract of Pirdot (Saurauia vulcani) (EES) in white rats induce rhodamine B and predict interaction of bioactive compound Pirdot to bind active site Keap1-Nrf2. Twenty- four Male Wistar rats (100-200 g) divided into four groups. Group P1 served as group control is administered with CMC 0.5%; group P2 is treated with Rhodamine B 750 mg/kg BW, Group KP1 administered EES 500 mg/kg BW; and Group KP2 is treated with EES 500 mg/kg BW+ Rhodamine B 750 mg/kg BW. Hematological parameters were assessed. The results revealed that red blood cell (RBC), white blood cell (WBC), thrombocyte count, and hemoglobin concentration (Hb) in rats induced Rhodamine B significantly lower than the control group. However, EES could improve the value of hematological profile. Our finding demonstrated that EES normalizes the value of hematological parameters in rats induce Rhodamine B. Moreover, beta-amyrin, pomolic acid and maslinic acid from Pirdot had good binding affinity to Keap1-Nrf2